Fibroblast growth on patterned polymeric coatings. Issue 6 (23rd December 2015) - Genzel, Susanne; Sen‐Richter, Aromita; Reich, Uta; Menzel, Henning; Reuter, Günter; Lenarz, Thomas; Paasche, Gerrit
Abstract : Cochlear implantation enables many patients to hear again after severe to profound sensorineural hearing loss. Despite great success there is huge variability in outcome between patients. One of the reasons for this might be the interface between stimulating electrode and surrounding tissue. Fibrous tissue is formed around the electrode array after implantation and causes an increase in electrical impedance. Currently there are several approaches under investigation to address this issue. Amongst them are surface coatings but also surface patterning. The aim of the current study was therefore to investigate a number of polymeric coatings for their ability to reduce fibroblast growth and to investigate the influence of patterned surface coating on cell growth in vitro . Polymers were attached to the surface by the grafting onto method using a photoreactive anchor layer. Patterns (parallel polymer lines of different dimensions) were generated by selectively cross‐linking the polymer to the anchor molecules on the surface followed by removal of any excess polymer. EGFP producing fibroblasts were seeded on the surface and their growth was documented every day until complete coverage was achieved. A reduction in cell growth was observed for poly(ethyloxazoline) (PEtOx) and poly(dimethylacryl‐amide) (PDMAA) with only PDMAA resulting in coverage with cells of less than 25% indicating nearly complete growth inhibition when seeded on areas completely covered by polymer. Polymer lines of 5 μm width separated by 50 μm did not show a large influence on cell growth whereas lines of 12, 24, or 48 μm width separated by 50 μm had an influence on cell growth especially for PDMAA and PEtOx. This influence was most apparent on days 2 and 3 after seeding and vanished between days 4 and 7 depending on polymer and pattern. It was possible to suppress fibroblast growth on the surface by using polymeric coatings but a partial coating in the dimension used in the current study affected cell growth only for up to 1 week and would not be sufficient to reduce fibroblast growth permanently after implantation.